The role of collaborative work in the development of elementary students’ writing skills (2013)
In this article we report the findings of a two-phase action research study focused on the role of collaborative work in the development of elementary students’ writing skills at a Colombian school. This was decided after having identified the students’ difficulties in the English classes related to word transfer, literal translation, weak connection of ideas and no paragraph structure when communicating theirideas. In the first phase teachers observed, collected, read and analyzed students’ written productions without intervention. In the second one, teachers read about and implemented strategies based on collaborative work, collected information, analyzed students’ productions and field notes in order to finally identify new issues, create and develop strategies to overcome students’ difficulties. Findings show students’ roles and reactions as well as task completion and language construction when motivatedto work collaboratively.Presentamos los resultados de una investigación-acción llevada a cabo en dos fases, centrada en el papel del trabajo colaborativo en el desarrollo de habilidades de escritura de estudiantes de primaria en una escuela colombiana. El estudio se realizó tras haber identificado las dificultades de los alumnos en las clases de inglés relacionadas con la transferencia de palabras, la traducción literal, la débilconexión de las ideas y la falta de estructura del párrafo al comunicar sus ideas. En la primera fase los docentes observaron, recogieron, leyeron y analizaron las producciones escritas de los alumnos sin realizar ninguna intervención pedagógica. En la segunda, los profesores leyeron sobre estrategias de trabajo colaborativo y las implementaron; recopilaron información, analizaron las producciones textuales de los estudiantes y las notas de campo tomadas para identificar nuevos problemas, creary desarrollar estrategias que ayudaran a los estudiantes a superar sus dificultades. Los hallazgos muestran cómo reaccionaron los estudiantes ante el trabajo colaborativo, y asimismo la forma como realizan tareas y construyen su lenguaje cuando están motivados a trabajar de esta manera.